A high-end sea level rise probabilistic projection including rapid Antarctic ice sheet mass loss. (3rd April 2017) - Le Bars, Dewi; Drijfhout, Sybren; de Vries, Hylke
Abstract: The potential for break-up of Antarctic ice shelves by hydrofracturing and following ice cliff instability might be important for future ice dynamics. One recent study suggests that the Antarctic ice sheet could lose a lot more mass during the 21st century than previously thought. This increased mass-loss is found to strongly depend on the emission scenario and thereby on global temperature change. We investigate the impact of this new information on high-end global sea level rise projections by developing a probabilistic process-based method. It is shown that uncertainties in the projections increase when including the temperature dependence of Antarctic mass loss and the uncertainty in the Coupled Model Intercomparison Project Phase 5 (CMIP5) model ensemble. Including these new uncertainties we provide probability density functions for the high-end distribution of total global mean sea level in 2100 conditional on emission scenario. These projections provide a probabilistic context to previous extreme sea level scenarios developed for adaptation purposes.